Seismic Behaviour of Tall Structures with RC Shear Walls and Columns Configuration by ETABS (2021) (Global Journals of Research in Engineering, 2023)
Shear wall System Commonly used in the Tall Structures to resist Sustain the Lateral forces Exerted due to Winds Earthquakes Due to Shear Wall s high in-Plane Stiffness and Simultaneously has Capacity to take Gravity Loads Inclusion of Shear Wall has become very inevitable in Tall Structures to resist Lateral forces It is important necessary to Find the Structural Configuration is effectively Safe or not Hence In this article The Structural analysis is conducted on Basement G 31 Tall Building of Total Height of 108m in order to determine the Base Shear Maximum Storey Displacement Maximum Storey Drifts Storey Shears Overturning Moments and Axial Forces over the Critical Load Combination For this Purpose different zones are selected to investigate the effect of Lateral Forces If Building is Either on Shear Wall Configuration or on Column Configuration A detailed study on behaviour of both columns and RC Shear Wall is conducted with eight model made on CSI ETABS 2021 Software in the present study Building models included with Shear Wall Configuration in different seismic Zones and Column Configuration in different Seismic Zone Each of these models has Subjected to Response Spectrum method of Analysis as referred in IS 1893 2016 Building is assumed as Commercial building located in all Seismic Zones of India The comparison of analysis results shows that how both Type of buildings are performing under lateral or seismic loads in Different Seismic zones and determining the seismic parameters like base shear Max Storey displacement Max Storey drifts Storey Shear Overturning Moments and Axial forces are checked out under the Critical Load Combination In this present study software results shown Max Storey displacement 38 lesser Max Storey drifts 38 and Axial reaction 19 lesser in case of Shear wall Storey Shear 3 Overturning Moments 4 and Base Shear 3 greater in case of shear Wall Configuration which is marginal
Keywords: RC shear wall; base shear; max storey drift; max storey displacement; storey shear; response spectrum method